Development and characterization of pramipexole dihydrochloride buccal films for Parkinson’s disease treatment - Krisztián Pamlényi; Bárbara Ferreira; Géza Regdon Jr.; Katalin Kristó; Bruno Sarmento (PLoS ONE, 2025)
Parkinson’s disease is one of the most common neurodegenerative diseases worldwide. Swallowing difficulties present a significant challenge in the treatment of Parkinson’s disease patients. Our current experimental work aimed to produce and assess a buccal polymer film containing pramipexole as the active pharmaceutical agent. This dosage form addresses the swallowing difficulties faced by Parkinson’s patients, potentially eliminating inappropriate drug application and thereby improving therapeutic success. For the preparation of polymer films, chitosan was used as the film-forming agent, and pramipexole dihydrochloride was the active pharmaceutical ingredient. The physical properties of the prepared polymer films, such as thickness, tensile strength, mass, and disintegration time were examined, along with in vitro mucoadhesivity. The chemical interactions between the different components of the films were analyzed using FTIR spectroscopy. Additionally, the dissolution of pramipexole from the polymer film and the permeation of the active ingredient through the TR146 buccal cell line were investigated. Finally, the biocompatibility of the prepared polymer films was also tested on a buccal cell line. The results indicate that increasing the concentration of glycerol reduced the tensile strength and mucoadhesion of the films to 12 kPa and 7 N, respectively. Interactions between the components of films were confirmed by FTIR analysis. All formulations demonstrated biocompatibility higher than 80%. Based on different investigations, Sample 4 and Sample 5 are suitable for buccal application. These formulations exhibit promising attributes for treating Parkinson’s disease.